Dimensional coordination in the construction industry: the need of IT in Malaysia / Afridah Riduan and Norizan Abd Aziz - Riduan, Afridah; Abd Aziz, Norizan (1985)
A chapter of joints is devoted in order to stress the problem of joints in the selection of modular components.